2007
DOI: 10.1007/s10461-007-9324-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Maternal Communication with Preadolescents about Age-Relevant Sexual Topics

Abstract: The present study examined factors that promote parent-child discussions about sex topics. A sample of 1,066 dyads of African American mothers and their 9-12-year-old children participated completing computer-administered surveys. After controlling for all other covariates, mother's sexual communication responsiveness (i.e., knowledge, comfort, skills, and confidence) was the most consistent predictor of discussions. Mothers with higher responsiveness had significantly increased odds of discussions about absti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 27 publications
6
56
0
2
Order By: Relevance
“…This constellation of skills, comfort and confidence is consistently associated with both the occurrence and effectiveness of parent-child communication about sexual issues [9][10][11][12]40]. The current study adds to the literature by demonstrating the importance of responsiveness when communicating about a specific sexual topic, HIV/AIDS, and by demonstrating its cross-cultural relevance.…”
Section: Discussionmentioning
confidence: 59%
“…This constellation of skills, comfort and confidence is consistently associated with both the occurrence and effectiveness of parent-child communication about sexual issues [9][10][11][12]40]. The current study adds to the literature by demonstrating the importance of responsiveness when communicating about a specific sexual topic, HIV/AIDS, and by demonstrating its cross-cultural relevance.…”
Section: Discussionmentioning
confidence: 59%
“…Past research has shown that mothers talk to teens about sex more than fathers, daughters are more likely to be the targets of sexual communication, and communication about sexual topics is more effective if it takes place before teens engage in sexual activity. It is important that parents should be open and comfortable while talking to their teens [16,[19][20][21][22].…”
mentioning
confidence: 99%
“…Sexual risk communication varies in frequency and content depending on the age of the child. A study by Miller et al chose to examine barriers to communication in preadolescents (9-12 years old) based on the finding that sexual activity increases with age, and characterized of early sexual initiation as sex prior to age 13 (Miller, Fasula, Dittus, Wiegand, Wyckoff, & McNair, 2009). The authors found that the mother's responsiveness (i.e.…”
Section: Demographic Factorsmentioning
confidence: 99%